2021
DOI: 10.21203/rs.3.rs-403120/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How do the Pore Traits of Hardwoods Affect Sound Absorption Performance of their Cross Sections? - Focusing on 6 Species of Korean Hardwoods

Abstract: An investigation of sound absorption in 6 species of hardwoods according to the pore structure of cross-sections revealed that higher gas permeability was associated with greater sound absorption at high frequencies. In addition, diffuse-porous wood exhibited superior sound absorption performance compared with ring-porous wood. Through-pore porosity was associated with improved sound absorption in the cross-sections of all 6 species, while closed-pore porosity was associated with poor sound absorption. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Wood and forest-by products have been suggested as a natural sound-absorbing materials (Iswanto et al, 2020;Jang, 2022aJang, , 2022bJang, , 2022dJung et al, 2020;Jung et al, 2021). Previous studies have reported that the pore structure of wood has a sound-absorbing effect (Jang and Kang, 2021a, 2021dJiang et al, 2004;Taghiyari et al, 2014). When wood is subjected to heat treatment such as high-temperature oven-drying, microwave, or steam explosion, the pores are converted into an open-pore structure, and the sound absorption performance can be further improved (Jang and Kang, 2021b;Jang and Kang, 2022;Kang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wood and forest-by products have been suggested as a natural sound-absorbing materials (Iswanto et al, 2020;Jang, 2022aJang, , 2022bJang, , 2022dJung et al, 2020;Jung et al, 2021). Previous studies have reported that the pore structure of wood has a sound-absorbing effect (Jang and Kang, 2021a, 2021dJiang et al, 2004;Taghiyari et al, 2014). When wood is subjected to heat treatment such as high-temperature oven-drying, microwave, or steam explosion, the pores are converted into an open-pore structure, and the sound absorption performance can be further improved (Jang and Kang, 2021b;Jang and Kang, 2022;Kang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%